Late Holocene hydroclimatic variation in central Asia and its response to mid-latitude Westerlies and solar irradiance. (15th June 2020) - Lan, Jianghu; Zhang, Jin; Cheng, Peng; Ma, Xiaolin; Ai, Li; Chawchai, Sakonvan; Zhou, Kang'en; Wang, Tianli; Yu, Keke; Sheng, Enguo; Kang, Shugang; Zang, Jingjie; et al.
Abstract: Hydroclimatic variations in central Asia are widely recognized to be tele-connected with the North Atlantic climate via the mid-latitude Westerlies. However, the long-term hydroclimatic variation and its response to North Atlantic climate changes are not fully understood. Here we report multi-decadal and centennial hydroclimatic variations in central Asia during the late Holocene using high-resolution oxygen and carbon isotopes of bulk carbonate from a remote hydrologically closed alpine lake in Tianshan Mountains, northwestern China. The hydroclimatic variations inferred from the covariance between δ 18 Ocarb and δ 13 Ccarb and published multi-proxy in the Lake Sayram together agree well with the records from the central Asia, showing enhanced effective moisture at the intervals of 4000-3780, 3590-3210, 2800-2160, 1700-1370 and 890-280 cal yr BP during the negative phase of North Atlantic Oscillation (NAO). Comparison with European hydroclimatic changes on centennial scale, our records not only provide valuable insight into the hydroclimatic variations in central Asia, but also indicate all broadly contemporaneous changes with that of southern Europe whereas antiphase with that of northern Europe. We then conclude that the observed antiphase hydroclimatic pattern between northern Europe and southern Europe-central Asia on centennial time scale during the late Holocene were persistently controlled by the north-south migration of mid-latitude Westerlies and changes of NAO phase in response to solar irradiance forcing. However, further research is necessary to fully disentangle the natural and anthropogenic forcing mechanisms for enhanced effect moisture and/or precipitation in central Asia. Highlights: Paired δ 18 Ocarb and δ 13 Ccarb revealed enhanced effective moisture during the negative phase of NAO. The hydroclimate in central Asia were contemporaneous with that of S Europe whereas antiphase with that of N Europe. The hydroclimate in central Asia were contemporaneous with that of S Europe whereas antiphase with that of N Europe.